A case study on sonic heritage and acoustic profiling of the bamboo bass guitar - Ahmad Faudzi, Musib; Aaliyawani E., Sinin; Sinin, Hamdan; Khairul Anwar, Mohamad Said (NC State University, 2025)
The acoustic properties of a custom-built bamboo bass guitar (BBG) were examined in this study as a sustainable substitute for traditional wooden instruments. To evaluate tonal and harmonic behavior, the BBG which was made completely of bamboo components was contrasted with the Fender Jazz Bass ’70s (FJB70s). While spectrograms from Adobe Audition offered visual insight into overtone distribution, frequency spectrum data were recorded using a PicoScope oscilloscope and subjected to Fast Fourier transform (FFT) analysis. Although the BBG’s pitch and harmonic series matched those of the FJB70s, its timbre was noticeably different, with less radiation and more damping. Throughout the spectrum, its overtone amplitudes gradually decreased, while the FJB70s’ harmonic presence remained increasingly distinct and steady. In the BBG signal, random partials that show up in between harmonic peaks indicate variations in structural resonance. These results lend credence to bamboo’s potential as an acoustic material for bass instruments, providing unique sound textures and encouraging environmental sustainability.